Changes in circulating follicular helper T-cells in Chinese patients with allergic rhinitis. (1st February 2016) - Wang, Xiao-Qiang; Ke, Xia; Shen, Yang; Kang, Hou-Yong; Gu, Zheng; Hu, Guo-hua; Hong, Su-Ling
Abstract: Conclusions : Changes of circulating Follicular helper T (cTfh) cells existed in allergic rhinitis (AR) patients, and the severity of disease was associated with a more severe change of cTfh milieu. These results imply that cTfh cells may play a crucial role in the pathology of AR in Chinese patients. Objectives : The aim of this study was to investigate the changes in cTfh cells in Chinese AR patients. Methods : Fifty-two patients were studied (32 in the AR group and 20 in the control group) for this research. The cTfh cell frequency and mRNA levels of transcription factor Bcl-6, B lymphocyte induced maturation protein 1 (BLIMP-1), and related cytokine IL-21 (IL-21 protein was also measured) were analyzed. Clinical severity was evaluated by total serum IgE levels, visual analog scale scores (VAS), and rhino-conjunctivitis quality-of-life questionnaires (RQLQ). Results : The frequency of cTfh cells were elevated in AR groups vs healthy controls ( p  < 0.05). Levels of IL-21 mRNA, Bcl-6 mRNA and the level of IL-21 protein were also significantly higher in the AR groups ( p  < 0.05), whereas BLIMP-1 mRNA was decreased ( p  < 0.05). Furthermore, positive correlations were identified between the frequency of cTfh cells and indicators of clinical severity ( p  < 0.01).